2021
DOI: 10.1007/s11427-021-1975-9
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Hedgehog pathway by compartmentalized PKA in the primary cilium

Abstract: The Hedgehog (Hh) signaling is one of the essential signaling pathways during embryogenesis and in adults. Hh signal transduction relies on primary cilium, a specialized cell surface organelle viewed as the hub of cell signaling. Protein kinase A (PKA) has been recognized as a potent negative regulator of the Hh pathway, raising the question of how such a ubiquitous kinase specifically regulates one signaling pathway. We reviewed recent genetic, molecular and biochemical studies that have advanced our mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 180 publications
(261 reference statements)
0
6
0
Order By: Relevance
“…SMO inhibition of PKA-C is fundamental to Hh signal transduction in development, homeostasis, and disease [2][3][4]34 . Here we identify GRK2 as an indispensable regulator of this inhibition during Hh signal transduction in primary cilia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SMO inhibition of PKA-C is fundamental to Hh signal transduction in development, homeostasis, and disease [2][3][4]34 . Here we identify GRK2 as an indispensable regulator of this inhibition during Hh signal transduction in primary cilia.…”
Section: Discussionmentioning
confidence: 99%
“…In the pathway "on" state, Hh proteins bind to and inhibit PTCH1, enabling SMO to bind sterols [26][27][28][29] , assume an active conformation [26][27][28][29] , and accumulate to high levels in the cilium [30][31][32] . Active SMO blocks PKA-C phosphorylation of GLI, leading to GLI activation 22,24,25,33,34 . SMO inhibition of PKA-C is thus fundamental to Hh signal transduction, but the underlying mechanism has remained poorly understood, mainly because it does not rely on the standard signaling paradigms employed by nearly all other GPCRs [35][36][37] .…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, a recent study showed that neuropilin 2 (Nrp2), an axon guidance molecule, plays crucial roles in instructing circuit formation from the MOB to MeA for the transmission of attractive social signals in the brain ( Inokuchi et al., 2017 ). Given that the role of both neuropilin 1 (Nrp1) and its ligand Sema-3A in axon guidance processes toward the MOB depends on functional ciliary AC3-mediated cAMP signaling in the MOE ( Col et al., 2007 ; Henion et al., 2011 ; Imai et al., 2009 ; Schwarting and Henion, 2011 ) and is associated with cilium-related Hedgehog signaling ( Cai et al., 2021 ; Hillman et al., 2011 ; Pinskey et al., 2017 ) and that the ablation of neuropilin and its ligand in mice leads to pleiotropic phenotypes ( Assous et al., 2019 ; Cariboni et al., 2007 ; Demyanenko et al., 2014 ; Duncan et al., 2021 ; Li et al., 2019 ; Maden et al., 2012 ; Mohan et al., 2018 , 2019 ; Riccomagno et al., 2012 ; Tan et al., 2019 ; Tran et al., 2009 ; van der Klaauw et al., 2019 ; Vanacker et al., 2020 ) that mirror the functions of AC3 in multiple brain areas, we hypothesize that the pleiotropic phenotypes illustrated in these AC3-deficient mice, including the defects in infanticidal behaviors observed in this study, might be caused by cilia-associated neuropilin signaling in a brain region-specific and cell type-specific manner. Collectively, the results indicate that similar to other ciliopathy-associated proteins, AC3 could be reasonably identified as a key player in associated ciliopathies, although why and how unique ciliary AC3-mediated cAMP signaling plays multiple functions across different brain areas and neuronal subtypes, including the infanticidal behaviors involved in the MOE, AON, and VMH regions, remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…While we summarized studies on the core components of the Hh pathway during brain development, numerous studies have reported that other Hh modulators act to refine Hh signaling during brain development. One such important regulator is PKA, a potent Hh signaling suppressor that regulates the pathway by controlling Gli activation [ 95 ]. Genetic knockout of both isoforms of the PKA catalytic submit ( Cα and Cβ ) results in full activation of Hh signaling, leading to an open and ventralized neural tube resembling the phenotypes of Ptch1 knockout [ 4 ].…”
Section: Roles Of Hedgehog Signaling During Cortical Developmentmentioning
confidence: 99%